2003
DOI: 10.1079/bjn2003895
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variation of basal metabolic rate and the influence of daily habitual physical activity before testing

Abstract: The present study determined the intra-individual variation of BMR measurements, using a standard out-patient protocol, with the subjects transporting themselves to the laboratory for the BMR measurements after spending the night at home. The effect of a non-fasting state and variation in daily habitual physical activity the day before testing was evaluated. Eight male and eleven female subjects participated in three BMR measurements with 2-week intervals. Physical activity was estimated with a tri-axial accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 30 publications
7
58
0
Order By: Relevance
“…No repeat assessments of BMR were included in this study. However, previous studies have indicated that within-individual variation in BMR is typically less than 8%, although it is generally greater among women (Henry et al, 1989;Spurr et al, 1994;Adriaens et al, 2003).…”
Section: Basal Metabolic Rate (Bmr)mentioning
confidence: 94%
“…No repeat assessments of BMR were included in this study. However, previous studies have indicated that within-individual variation in BMR is typically less than 8%, although it is generally greater among women (Henry et al, 1989;Spurr et al, 1994;Adriaens et al, 2003).…”
Section: Basal Metabolic Rate (Bmr)mentioning
confidence: 94%
“…A plausible energy intake reporter was defined as a child with 0.7 × TEI ≥ BMR. As the estimation of BMR and the cutoff used to differentiate underreporters and plausible energy intake reporters may not be entirely accurate [31], this variable was not included in the final models, but rather was used for descriptive and sensitivity analyses only.…”
Section: Methodsmentioning
confidence: 99%
“…Gas analyses were performed with a paramagnetic oxygen analyzer (Servomex, type 1158) and an infrared carbon dioxide analyzer (Servomex, type 1520) while flow was kept at a constant rate of 80 L/min and additionally measured as described by Schoffelen et al (24). The withinindividual CV for this system is 3.3 6 2.1% (25). Calculation of RMR from measured oxygen consumption and carbon dioxide production was based on Brouwer's formula (26).…”
Section: Rmrmentioning
confidence: 99%